Prostate cancer cells differ in testosterone accumulation, dihydrotestosterone conversion, and androgen receptor signaling response to steroid 5α‐reductase inhibitors12. Issue 13 (27th June 2013) - Wu, Yue; Godoy, Alejandro; Azzouni, Faris; Wilton, John H.; Ip, Clement; Mohler, James L.
Abstract BACKGROUND Blocking 5α‐reductase‐mediated testosterone conversion to dihydrotestosterone (DHT) with finasteride or dutasteride is the driving hypothesis behind two prostate cancer prevention trials. Factors affecting intracellular androgen levels and the androgen receptor (AR) signaling axis need to be examined systematically in order to fully understand the outcome of interventions using these drugs. METHODS The expression of three 5α‐reductase isozymes, as determined by immunohistochemistry and qRT‐PCR, was studied in five human prostate cancer cell lines. Intracellular testosterone and DHT were analyzed using mass spectrometry. A luciferase reporter assay and AR‐regulated genes were used to evaluate the modulation of AR activity. RESULTS Prostate cancer cells were capable of accumulating testosterone to a level 15–50 times higher than that in the medium. The profile and expression of 5α‐reductase isozymes did not predict the capacity to convert testosterone to DHT. Finasteride and dutasteride were able to depress testosterone uptake in addition to lowering intracellular DHT. The inhibition of AR activity following drug treatment often exceeded the expected response due to reduced availability of DHT. The ability to maintain high intracellular testosterone might compensate for the shortage of DHT. CONCLUSIONS The biological effect of finasteride or dutasteride appears to be complex and may depend on the interplay of several factors, which include testosterone turnover, enzymology of DHT production, ability to use testosterone and DHT interchangeably, and propensity of cells for off‐target AR inhibitory effect. Prostate 73: 1470–1482, 2013. © 2013 Wiley Periodicals, Inc.